An Examination Of The Impact Of Return On Equity (Roe) And Return On Assets (Roa) On Ntb Syariah Bank's Profit Growth - Renaldy, Lalu; Aziz, Rusman Azizoma; Yusrini, Baiq Ari; Suriani, Suriani (IQTISHADUNA, 2024)
This study aims to determine the effect of Return On Assets and Return On Equity on Profit Growth . This study uses a quantitative method that emphasizes the proof of the hypothesis which is based on the formulation of the problem presented. Data collection techniques are carried out by collecting data obtained from the official website of Bank NTB Syariah. Data analysis was carried out using an analytical tool, namely E-views. Based on the results of the t-test, the probability value of X1 Return On Assets (ROA) is 0.0000 which means that the probability value is less than 0.05, so it can be said that the Return On Assets (ROA) has a significant effect, and has a coefficient value of 4.710385, so it can be said that Return On Assets (ROA) has a positive effect. The results of this study indicate that Return on Assets (ROA) (XI) has a positive and significant effect on Profit Growth (Y). Based on the results of the t-test, the probability value of X2 Return On Equity (ROE) is 0.0051 which means that the probability value is less than 0.05, so it can be said that Return On Equity (ROE) has a significant effect, and has a coefficient value of -0.379687, so it can be said that (Return On Equity (ROE) has a negative effect. The results of this study indicate that Return On Equity (ROE) has a negative and significant effect on Profit Growth (Y).